2017
DOI: 10.1177/2167479517719683
|View full text |Cite
|
Sign up to set email alerts
|

A “Crucial Catch”

Abstract: This study investigated the National Football League’s (NFL) communication efforts of its annual Corporate Social Responsibility (CSR) campaign, “A Crucial Catch,” and the subsequent social media engagement from the public. A content analysis was conducted examining how NFL teams communicate their CSR efforts on Facebook using Charity Support Behaviors (CSB) and framing as our guide and then measuring which of these types of social media posts were most effective for increasing positive social media engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Past research has confirmed that the level of team identification can significantly and positively influence sports consumption behavior [104]. Specifically, sports consumers with high team identification provide more significant support for the team they identify with by watching more games, purchasing more merchandise symbolizing the team, and buying products from their sponsors than sports consumers with low team identification [48,50,105]. Recent research has revealed new findings that the message type of advertising can be classified as hedonic and meaningful when athlete-owned foundations highlight the happy or meaningful aspects of the athletes in their promotional ads.…”
Section: The Impact Of Team Identification On Meaningful Sports Consu...mentioning
confidence: 97%
“…Past research has confirmed that the level of team identification can significantly and positively influence sports consumption behavior [104]. Specifically, sports consumers with high team identification provide more significant support for the team they identify with by watching more games, purchasing more merchandise symbolizing the team, and buying products from their sponsors than sports consumers with low team identification [48,50,105]. Recent research has revealed new findings that the message type of advertising can be classified as hedonic and meaningful when athlete-owned foundations highlight the happy or meaningful aspects of the athletes in their promotional ads.…”
Section: The Impact Of Team Identification On Meaningful Sports Consu...mentioning
confidence: 97%
“…Pinkwashing is the first of these and has been applied to two quite different areas. In the first case, corporate actors have been criticized for using the pink logo of various breast cancer charities on their products when they do not actually contribute (Carter, 2015) or contribute very little to these charities (Devlin and Sheehan, 2018). However, in the academic literature, pinkwashing is most strongly associated with corporations, and to a lesser extent governments, that emphasise their support of LGTBQ people and lifestyles in order to either access the ‘pink pound’ (Elliot, 2007; Fry, 1997) or to brand themselves as tolerant, open and progressive.…”
Section: Washing As Metaphormentioning
confidence: 99%